Електрохімічна поведінка псевдосплаву WC-Co в розчинах сульфатної кислоти - Османова, Марина Павлівна; Тульський, Геннадій Георгійович; Ляшок, Лариса Василівна; Колупаєв, Ігор Миколайович (Дослідно-видавничий центр Наукового товариства ім. Шевченка, 2018)
The electrochemical behavior of the WC-Co pseudo-alloy in acid solutions of H2SO4 was studied. The method of processing a solid tungsten-cobalt alloy in a solution of 4M H2SO4 with a 0.2 – 0.3 M content of a reducing agent-hexamine is proposed, it allows to obtain a tungsten powder in a slurry.
Electrochiological Behavior of Pseudoalloys Wc–Co in Sulfuric Acid Solutions
Keywords: вольфрам; кобальт; сплави; сульфатна кислота; псевдосплави; secondary tungsten-containing raw materials; anodic disolution; polarization dependence; acidic electrolyte; електроліти